The Current State of the Landscaping System of a Large Industrial Center (for Example, the City of Krasnoyarsk). Issue 4 (March 2021) - Avdeeva, E; Kuhar, I; Chernikova, K
Abstract: An important indicator of the state of comfort of urbanized territories is the provision of city residents with green areas. Green areas of common use include plantings of city-wide and district parks, inter-quarter gardens, squares, boulevards and embankments. Currently Krasnoyarsk is one of the largest centers in Eastern Siberia. Historical and new areas of Krasnoyarsk differ significantly from each other by the nature of landscaping. Protective zones located between residential and industrial areas along highways and railways should make a great contribution to the general greening system of the city. Analysis of the dendrological composition and distribution of species in plantings of the city shows that the main composition of plantations is represented by a limited number of species, among which balsam poplar and ash-leaved maple are unpromising species for plantings of general and limited use. The list of woody plants recommended for landscaping the city, tested in arboretums, plantations of the central part of the city and Akademgorodok, is represented by a fairly large variety, including both local species and species of various botanical and geographical regions. At the same time, an increase in the share of the main forest-forming species in the greening of urban areas, such as drooping birch, Siberian larch, Siberian spruce, their high decorative qualities will allow to more fully solve the problem of forming the individual appearance of a Siberian city. The combination of these rocks with the natural components of the landscape - relief, bodies of water and artificial elements (buildings, engineering structures) - will increase the artistic expression of urban development.